Cardiac device-induced right to left shunt causing significant hypoxemia: A case report and review of literature. (2022) - Salick, Muhammad; Anwar, Raheel; Pani, Saroj; Adelstein, Evan; El-Hajjar, Mohammad; Fein, Steven; Judson, Marc
Abstract: We describe a patient where a pacemaker lead induced tricuspid valve changes that caused a right to left shunt through a preexisting patent foramen ovale resulting in significant hypoxemia. This event occurred years after the pacemaker had been placed. Surgical closure of the patent foramen ovale resolved the patient's hypoxemia and dyspnea. We also reviewed the previous cases published in the medical literature concerning significant hypoxemia from cardiac device-induced right to left shunts. Three of the four reported cased occurred 4 or more years after device placement. Therefore, late onset hypoxemia in setting of cardiac device placement without an alternative cause should raise the possibility of this complication.